Effect of Permeability on Magnetoelectric Effect - Liu, Xiaoxia; Zhang, Liwen; Xu, Jiawei (2023 5th International Conference on Electronic Engineering and Informatics (EEI), 2023)
The subject to be studied is the impact of permeability on bias magnetic field and frequency response characteristics of magnetoelectricity effect in ferromagnet/piezoelectric ceramic composite structure. Through experiment and analysis, this paper introduces the preparation of samples, the knowledge of measuring devices (UHF PLA), and the use of drawing software (Origin). Finally, this study draws a conclusion and prospects the influence of AC susceptibility on the frequency response characteristics, resonant frequency, and the resonant peak of the sample.